2021
DOI: 10.2147/jpr.s310238
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Spondylolisthesis Progression: What is the Effect of Lumbar Medial Branch Nerve Radiofrequency Ablation on Lumbar Spondylolisthesis Progression? A Single-Center, Observational Study

Abstract: Background Radiofrequency ablation (RFA) is a denervation therapy commonly performed for pain of facet etiology. Degenerative spondylolisthesis, a malalignment of the spinal vertebrae, may be a co-existing condition contributing to pain; yet the effect of RFA on advancing listhesis is unknown. To the extent that denervating RFA may weaken paraspinal muscles that provide stability to the spine, the therapy can potentially contribute to progressive spinal instability. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…This gender distribution is in line with other earlier research that found that men were more likely than women to develop spondylolisthesis. 12 While in contrast, one other study reported the prevalence of degenerative spondylolisthesis and its ratio greater in females than in men (3:1). 13 The mean age of the study population was 45 years, falling within the range reported in the literature.…”
Section: Discussionmentioning
confidence: 91%
“…This gender distribution is in line with other earlier research that found that men were more likely than women to develop spondylolisthesis. 12 While in contrast, one other study reported the prevalence of degenerative spondylolisthesis and its ratio greater in females than in men (3:1). 13 The mean age of the study population was 45 years, falling within the range reported in the literature.…”
Section: Discussionmentioning
confidence: 91%